Medium Small Micro Enterprise (MSME) Development and Economic Growth: Causality Analysis - Gentur Jalunggono; Retno Sugiharti; Fitrah Sari Islami; Puji Aisyah Zahroti (Optimum: Jurnal Ekonomi dan Pembangunan, 2022)
As a business sector with a fairly large contribution to national output, government support for Micro, Small, Medium Enterprises (MSMEs) is increasingly being increased, even though the ratio of MSME credit to total national credit is still very small.  Capital difficulties are a classic problem faced by MSMEs, but the high growth of MSMEs is a gap that shows the resilience of MSMEs. Therefore, this study wants to analyze whether the existence of MSMEs encourages economic growth, or vice versa, economic growth must be boosted to increase MSMEs. This study investigates the causal relationship and long-term stability conditions between MSME credit distribution variables and Indonesia's economic growth in the 2011 - 2019 period, using Direct Error Correction Model causality on panel data. The estimation result shows that MSME credit distribution has a positive and significant relationship to economic growth only in a long term. On the other hand, the causal relationship between MSME credit and economic growth is not proven, which means that there is no reciprocal relationship between credit and economic growth, or said in here demand following hypothesis is not proven